Pentingnya Inovasi Media Pembelajaran Berbasis Digital di Abad-21 - Devyana Pratiwi; Annisa Novia Larasati; Imya Lesina Berutu (Program Studi Pendidikan Biologi, 2022)
This study aims to determine the importance of Digital-Based Learning Media Innovation in the 21st Century. The research method used in this study is library research with qualitative research. With the results of research that the use of technological developments that are all digital in the current era makes it easier for teachers to create innovative learning media that will be used by students in the learning process. One example of learning media innovation is Youtube, Microsoft Teams and Game Based Learning. Innovations are carried out as a form of sensitivity to existing technological advances, this can affect the learning process, namely how students can receive information or insights if the learning media provided is not digitized. Of course, the information obtained by students who use digital-based learning media will be different from those that do not.